Profile of Gut Bacteria in Hypertensive Patients Based on Terminal Restriction Fragment Length Polymorphism Analysis - Ririn Herni Putri; Rika Indri Astuti; Sri Budiarti (Bogor Agricultural University, Indonesia, 2023)
Hypertension is a severe public health problem due to its high prevalence worldwide. About 7.5 million deaths or 12.8% of all annual deaths worldwide occur due to high blood pressure. The hypertensive disease is also associated with the intestinal bacteria. To our knowledge, the diversity of the gut bacteria in hypertensive patients has not been reported yet in Indonesia. Thus, the aims of this study were to analyze profile of gut bacteria in hypertensive patients compared to non-hypertensive based on metagenomic analysis, Terminal Restriction Fragment Length Polymorphism (T-RFLP). The results of the affiliation analysis of the entire Terminal Restriction Fragments (TRF) contained 6 groups of bacteria from 26 TRFs in hypertensive and non-hypertensive respondents. Cutting the 16S rRNA gene with the BslI restriction enzyme successfully detected intestinal bacterial groups, namely Clostridium subcluster XIVa, Prevotella, Clostridium cluster IV, Clostridium cluster XI, Bacteroides and others. In hypertensive patients, a higher relative abundance of bacterial groups showed in Clostridium cluster XI, Clostridium cluster IV and Clostridium subcluster XIVa. The abundance of Bacteroides and Prevotella groups in hypertensive patients were lower than non-hypertensive. The abundance of enterotype I and enterotype II was lower in hypertensive patients than non-hypertensive. Contrarily to that enterotype III cluster. It is worth noting that the F/B ratio was higher in hypertensive patients than that in non-hypertensive. Our data suggest that the gut bacteria profile of hypertensive patients differs to that non-hypertensive.